The Dichotomy of Knowledge In Islamic Education: An Analysis Of The Existence Of The Faculty Of Tarbiyah And Teacher Training - Ahmad Maruf; Okta Nurma Vitriana; Suyadi (Insight School Academy, 2024)
Introduction to The Problem : The dichotomy between religious and general knowledge in Islamic education is fundamental. Islamic education programs must cover both domains to effectively nurture individuals proficient in Islamic teachings and have a broad understanding of public knowledge. Purpose : This study highlights the importance of integrating religious and general knowledge in Islamic education. It aims to underscore the importance of educational scholarship in promoting Islamic values and fostering competent Islamic educators. Design/methods/approach : This research utilizes a comprehensive literature review to explore the dichotomy between religious and general knowledge in Islamic education. Data collection, reduction, and analysis were conducted to provide insight into the challenges and opportunities faced by the Faculty of Tarbiyah and Keguruan in this regard. Findings The findings emphasize the importance of integrating Islamic education with general sciences to produce competent and fluent educators in Islamic teachings. Challenges such as incorporating technology and innovative learning methods are identified, along with suggestions to overcome them. Research implications/limitations : Here, you can explain characteristics of design or methodology that impacted or influenced the This study highlights the need for institutional collaboration, curriculum improvement, and teacher training to effectively integrate Islamic beliefs into the learning process. However, limitations may exist in the scope of the literature reviewed and the generalizability of the findings. Originality/value : By focusing on the intersection of religious and general knowledge in Islamic education, this research contributes to the ongoing discourse of educational reform in Islamic institutions. It underscores the importance of innovation, collaboration, and continuous improvement in promoting quality Islamic education relevant to contemporary society's needs.